If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.2p + 1.8p + 6 = 30 Reorder the terms: 6 + -0.2p + 1.8p = 30 Combine like terms: -0.2p + 1.8p = 1.6p 6 + 1.6p = 30 Solving 6 + 1.6p = 30 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 1.6p = 30 + -6 Combine like terms: 6 + -6 = 0 0 + 1.6p = 30 + -6 1.6p = 30 + -6 Combine like terms: 30 + -6 = 24 1.6p = 24 Divide each side by '1.6'. p = 15 Simplifying p = 15
| 3(5x-2)+9=10x-2 | | 2(5s+5)-4s=3(2s+6)-22 | | 4c+8=5.457479 | | x^4-10x^3-10x+26x^2+1=0 | | x^2+18x=9 | | 64r^2+128r-57= | | y^2-7y-44= | | 6x=5x-9 | | x^4+8x=y | | 3z=12-z | | -x^2+20x-91= | | -10=-12+0.57n | | .75x=16 | | 6p^4-32p^3+5p^2=0 | | 2x^3-19x^2=-9x | | 2(4t-1)+t=8-1 | | 5x^2+3x+10=0 | | 21x^2-10x-16= | | 11-3(a-1)=2+9 | | 11+78x+7x^2=0 | | 16y^2+48u+27=0 | | 11x-3=5x-4(1-2x) | | 2x+6/5=4 | | 49m+25m+49m= | | -18=4x-19 | | -6y+4=-2(4y+6) | | 14y^2-4y+3=0 | | 17x-9=12x+4 | | -3x^2-x+4=0 | | (4-x)=-11 | | x+3x^2-2= | | 3w^2+10w=-3 |